Pasteurisation temperatures effectively inactivate influenza A viruses in milk - Jenna Schafers; Caroline J. Warren; Jiayun Yang; Junsen Zhang; Sarah J. Cole; Jayne Cooper; Karolina Drewek; B. Reddy Kolli; Natalie McGinn; Mehnaz Qureshi; Scott M. Reid; Thomas P. Peacock; et al. (Nature Communications)
Abstract In late 2023 an H5N1 lineage of high pathogenicity avian influenza virus (HPAIV) began circulating in American dairy cattle Concerningly, high titres of virus were detected in cows’ milk, raising the concern that milk could be a route of human infection. Cows’ milk is typically pasteurised to render it safe for human consumption, but the effectiveness of pasteurisation on influenza viruses in milk was uncertain. To assess this, here we evaluate heat inactivation in milk for a panel of different influenza viruses. This includes human and avian influenza A viruses (IAVs), an influenza D virus that naturally infects cattle, and recombinant IAVs carrying contemporary avian or bovine H5N1 glycoproteins. At pasteurisation temperatures of 63 °C and 72 °C, we find that viral infectivity is rapidly lost and becomes undetectable before the times recommended for pasteurisation (30 minutes and 15 seconds, respectively). We then show that an H5N1 HPAIV in milk is effectively inactivated by a comparable treatment, even though its genetic material remains detectable. We conclude that pasteurisation conditions should effectively inactivate H5N1 HPAIV in cows’ milk, but that unpasteurised milk could carry infectious influenza viruses.